2022
DOI: 10.3390/cells11162512
|View full text |Cite
|
Sign up to set email alerts
|

Nano Modification of Antrodia Cinnamomea Exhibits Anti-Inflammatory Action and Improves the Migratory Potential of Myogenic Progenitors

Abstract: The skeletal muscle progenitors’ proliferation and migration are crucial stages of myogenesis. Identifying drug candidates that contribute to myogenesis can have a positive impact on atrophying muscle. The purpose of the study is to synthesize the Antrodia cinnamomea (AC)-β-cyclodextrin (BCD) inclusion complex (IC) and understand its in vitro pro-regenerative influence in murine skeletal C2C12 myoblasts. The IC was subjected to various nano-characterization studies. Fluorescent IC was synthesized to understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Compared with traditional Ganoderma lucidum, the contents of polysaccharides and triterpenes in Antrodia camphorata are far higher, which thus has good research value and application prospect [ 4 ]. There are numerous reports from Taiwan, Chin regarding the liver protective effect of Antrodia camphorata, and our previous study discovers that, Antrodia camphorata polysaccharides exhibit favorable protection against acute liver injury (ALI) [ 5 ]. At the same time, in the research on non-alcoholic fatty liver disease (NAFLD)-induced liver injury, Antcin A is found to exert its effect through suppressing NLRP3 inflammasome [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with traditional Ganoderma lucidum, the contents of polysaccharides and triterpenes in Antrodia camphorata are far higher, which thus has good research value and application prospect [ 4 ]. There are numerous reports from Taiwan, Chin regarding the liver protective effect of Antrodia camphorata, and our previous study discovers that, Antrodia camphorata polysaccharides exhibit favorable protection against acute liver injury (ALI) [ 5 ]. At the same time, in the research on non-alcoholic fatty liver disease (NAFLD)-induced liver injury, Antcin A is found to exert its effect through suppressing NLRP3 inflammasome [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Anticancer, anti−inflammatory, and anti−tumor effects are the main functions of T. camphoratus [62][63][64]. For this reason, it is very important to improve the culture efficiency of T. camphoratus mycelia instead of focusing on its fruit bodies and mycelia [65].…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticles drug delivery system can also improve the bioavailability of ergosterol following oral administration ( Zhang et al, 2016 ). AC modified the nanocarrier β-cyclodextrin (BCD) inclusion complex could potentially unlock its full potential and attempt to make it suitable for improving skeletal muscle health and possible to develop evidence-based drug ( Menon et al, 2022 ). The blood-brain barrier penetration of potential drugs is a critical issue, and delivery of these neuroprotective metabolites into the brain requires a tremendous effort, for which nanomedicine has emerged as a promising approach.…”
Section: Future Perspectivesmentioning
confidence: 99%